The Study of Abraham Ibn Daud in the Past Three Decades: What Do We (Not) Know? - Fontaine, Resianne (Anales del Seminario de Historia de la Filosofía, 2023)
The past three decades have witnessed a new and vivid interest in Ibn Daud. The bibliography in the entry devoted to this author in the Stanford Encyclopedia of Philosophy reveals that many studies on Abraham Ibn Daud and new editions of his writings were released between 1990 and the early 2020s. The aim of my contribution is to take stock of the results of the new research and to review how our knowledge of this multi-faceted author, the protagonist of the current publication, has been advanced in the past decades and where there are still gaps in our knowledge. Although I will discuss several aspects of Ibn Daud’s life, his activities, and the reception of his works, my focus will be on studies of his philosophical work.